Impact of serum lactate dehydrogenase on the short-term prognosis of COVID-19 with pre-existing cardiovascular diseases. Issue 4 (April 2022) - Masumoto, Akiko; Kitai, Takeshi; Matsumoto, Shingo; Kuroda, Shunsuke; Kohsaka, Shun; Tachikawa, Ryo; Seo, Ryutaro; Doi, Asako; Tomii, Keisuke; Yonetsu, Taishi; Torii, Sho; Komuro, Issei; et al.
Highlights: Patients with coronavirus disease 2019 (COVID-19) and underlying cardiovascular comorbidities have poor prognoses. Serum lactate dehydrogenase (LDH) is associated with mortality in acute respiratory distress syndrome. Serum LDH of 356 U/L or higher at hospital admission was independently associated with in-hospital mortality. High serum LDH may aid in triage of patients with COVID-19 and known cardiovascular disease. Abstract: Background: Patients with coronavirus disease 2019 (COVID-19) and underlying cardiovascular comorbidities have poor prognoses. Our aim was to identify the impact of serum lactate dehydrogenase (LDH), which is associated with mortality in acute respiratory distress syndrome, on the prognoses of patients with COVID-19 and underlying cardiovascular comorbidities. Methods: Among 1518 patients hospitalized with COVID-19 enrolled in the CLAVIS-COVID (Clinical Outcomes of COVID-19 Infection in Hospitalized Patients with Cardiovascular Diseases and/or Risk Factors study), 515 patients with cardiovascular comorbidities were analyzed. Patients were divided into tertiles based on LDH levels at admission [tertile 1 (T1), <235 U/L; tertile 2 (T2), 235–355 U/L; and tertile 3 (T3); ≥356 U/L]. We investigated the impact of LDH levels on the in-hospital mortality. Results: The mean age was 70.4 ± 30.0 years, and 65.3% were male. There were significantly more in-hospital deaths in T3 than in T1 and T2 [ n = 50 (29.2%) vs. n = 15 (8.7%), and n = 24 (14.0%), respectively; p < 0.001]. Multivariable analysis adjusted for age, comorbidities, vital signs, and laboratory data including D-dimer and high-sensitivity troponin showed T3 was associated with an increased risk of in-hospital mortality (adjusted hazard ratio, 3.04; 95% confidence interval, 1.50–6.13; p = 0.002). Conclusions: High serum LDH levels at the time of admission are associated with an increased risk of in-hospital death in patients with COVID-19 and known cardiovascular disease and may aid in triage of these patients. Graphical abstract: Image, graphical abstract